Serotonergic dysfunction in the A53T alpha‐synuclein mouse model of Parkinson's disease. (25th August 2015) - Deusser, Janina; Schmidt, Stefanie; Ettle, Benjamin; Plötz, Sonja; Huber, Sabine; Müller, Christian P.; Masliah, Eliezer; Winkler, Jürgen; Kohl, Zacharias
Abstract Parkinson's disease, neuropathologically defined by the aggregation of α‐synuclein, is characterized by neuropsychiatric symptoms such as depression and anxiety preceding the onset of motor symptoms. A loss of serotonergic neurons or their projections into the hippocampus and alterations in serotonin release may be linked to these symptoms. Here, we investigate the effect of human A53T α‐synuclein on serotonergic neurons using 12‐months‐old transgenic mice. We detected human α‐synuclein in the perikarya of brainstem median and dorsal raphe neurons as well as in serotonergic fibers in the hippocampus. Despite intracellular α‐synuclein accumulation there was no loss of serotonergic neurons in dorsal and median raphe nuclei of A53T α‐synuclein mice. However, serotonin levels were significantly reduced in the brainstem. In addition, serotonergic fiber density in the dorsal dentate gyrus was significantly less dense in transgenic mice. Interestingly, we detected a significantly compromised increase in doublecortin+ neuroblasts after chronic treatment with fluoxetine at the site of reduced serotonergic innervation, the infrapyramidal blade of the dorsal dentate gyrus in A53T α‐synuclein mice. This suggests that α‐synuclein affects serotonergic projections in a spatially distinct pattern within the hippocampus thereby influencing the response to antidepressant treatment. <boxed-text content-type="graphic" id="jnc13253-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text> A transgenic mouse model of Parkinson's disease (PD) shows α‐synuclein expression in serotonergic neurons of raphe nuclei. Besides lower serotonin levels in the raphe nuclei, a topographical restricted reduction in serotonergic fiber density was present in the hippocampus accompanied by an impaired fluoxetine‐response of hippocampal neuroblasts. In conclusion, α‐synuclein in the serotonergic system may account for psychiatric symptoms in PD. DR, dorsal raphe nucleus; MnR, median raphe nucleus.